Perkawinan Suku Dhawe Kabupaten Nagekeo Nusa Tenggara Timur Menurut Hukum Adat Dan Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan - Gamo, Emilia (JURNAL PROPERTY RIGHTS, 2014)
To know the marriage in Dhawe tribe and the maturity before getting married based on common on law for the people of Dhawe tribe in Nagekeo district is the part of Indonesian society who have norms and certain costoms. To describe n analyze the application a bout marriage conventional system of Dhawe tribe n the sign of maturity, giving the alternative, in order to know deeper the marriage processes according to the law conventional n positive law n to know the necessaries that are needed as the sign of respect for Dhawe tribe, in case of knowing the comparison n the difference between. Conventional law n positive law. The approximant method is sosiologi law whinch means to analyze various rule of laws that relate with relate with marriage based on conventional law of Nagekeo district.The problem solving in this theses by using the descriptive and qualitative methol. The data source is taken from the prime data that is directly taken fron the main source of the data or information given by the custom functioners. And the second data is the supporter data from the second source for the first data namely literature, legal documents, texts n library. The technical data collection is that the prime data is taken by doing interview about Dhawe tribeâs marriage to the custom missioners and society of Dhawe tribe by using respondent technique that are already united in note form meanwhile the secondary data is taken the is taken from the divining manual study such as document, internet, scientific journal and etc by learning and analyze the data. The technique of data analyze is used to express and analyze the description, condition and the development of conventional law aspect or Dhawe tribe in Nagekeo district. Meanwhile qualitative means the thinking process and to compare the one and another factors by concluding they view points of the writer.The result of application marriage system and the sign of maturity of Dhawe tribe in Nagekeo district that a girl is allowed to get married if she has fulfilled the maturity processes by being cut the teeth. She may follow some stages of marriage like tied application or conventional marriage and religious ceremonials. Thus the marriage conventional law is stated perfect. Meanwhile, the comparison between the conventional law about the marriage of Dhawe tribe in Nagekeo district according to the conventional law must be done and if the law is not being obeyed one will be punished according to the rules that are accepted in Dhawe tribe and as the part of national culture that causes the difference law as the social fenomena, seasonal, environment, insight and political pattern. While the similarity is caused by the existence of law and justice based on the constitution number 1 the year 1974 that is valid to tie the third side along it is noted in clausula or it is agreed marriage convention.